2018
DOI: 10.3988/jcn.2018.14.4.454
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Assessment of Neural Substrates in Computerized Cognitive Training: A Preliminary Study

Abstract: Background and PurposeSeveral studies have validated the clinical efficacy of computerized cognitive training applications. However, few studies have investigated the neural substrates of these training applications using simultaneous multimodal neuroimaging modalities. We aimed to determine the effectiveness of computerized cognitive training and corresponding neural substrates through a multimodal approach.MethodsTen patients with mild cognitive impairment (MCI), six patients with subjective memory impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…The insula, especially the anterior insula, is a critical node of the SN which connects many areas including the prefrontal cortex and the parietal lobe and engages in the transformation between cognitive domains (Cerliani et al, 2012 ). A study by Na et al reported that the MCI subgroup revealed focal activation in the left anterior insula and ACC after 24 sessions of computerized cognitive training (Na et al, 2018 ). The PreCG, which overlaps with the SMA, is involved in producing and controlling the movement (Cai et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The insula, especially the anterior insula, is a critical node of the SN which connects many areas including the prefrontal cortex and the parietal lobe and engages in the transformation between cognitive domains (Cerliani et al, 2012 ). A study by Na et al reported that the MCI subgroup revealed focal activation in the left anterior insula and ACC after 24 sessions of computerized cognitive training (Na et al, 2018 ). The PreCG, which overlaps with the SMA, is involved in producing and controlling the movement (Cai et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The populations with nCI exhibited one of the following risk factors: (1) subjective memory complaints/impairment (SMC/SMI) ( n = 3; Youn et al, 2009 ; Risacher et al, 2015 ; Na et al, 2018 ); (2) “probable MCI” defined by a mini-mental state examination (MMSE) score within normal range but a reduced Montreal cognitive assessment (MoCA) score ( n = 1; ten Brinke et al, 2015 ); (3) at-risk for dementia based on the CAIDE score (Cardiovascular Risk Factors, Aging, and Incidence of Dementia; Kivipelto et al, 2006 ) with cognitive performance at average or slightly lower level than expected according to Finnish population norms for Consortium to Establish a Registry for Alzheimer's Disease (CERAD) neuropsychological battery (Moms et al, 1989 ) ( n = 2; Stephen et al, 2019 , 2020 ); (4) limitations in one instrumental activity of daily living or slow gait speed or spontaneous memory complaints ( n = 1; Delrieu et al, 2020 ); (5) high systolic blood pressure ( n = 1; van Dalen et al, 2017 ); (6) elevated amyloid load or subthreshold amyloid levels [cerebral-to-cerebellar standard uptake value ratio (SUVR) threshold > 1.0; n = 1; Vidoni et al, 2021 ], or (7) hypertension and elevated amyloid load or subthreshold amyloid levels (SUVR > 1.0, see Vidoni et al, 2021 ) ( n = 1; Kaufman et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various CT were used, computerized ( n = 5) or non-computerized ( n = 8), uni- or multi-domain and aimed at improving domains such as memory, attention or executive functions. Over the five computerized CT, four targeted multiple cognitive domains (Barban et al, 2017 ; Na et al, 2018 ; Li et al, 2019 ; Zhang et al, 2019 ) while only one focussed on solely improving working memory (Vermeij et al, 2016 ). Among the eight non-computerized CT, two used multi-domain CT (Ciarmiello et al, 2015 ; Park et al, 2019 ), one included both multi-domain and uni-domain (Feng et al, 2018 ), and five tested single domains (Belleville et al, 2011 ; Yang et al, 2016 ; Hohenfeld et al, 2017 ; Simon et al, 2018 ; Youn et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations